ANALISIS PENGARUH KEBISINGAN TERHADAP GANGGUAN PENDENGARAN PEKERJA DI PT XYZ - Gusnaidi, Aldi; Zetli, Sri (Computer Science and Industrial Engineering, 2024)
The increasing use of technology in the industrial world has another significant impact on the occupational health and safety of workers. A work environment that is too noisy can lead to counter-productive, unhealthy, and upsetting situations. Based on the measurement results in the extruder machine area obtained with an average value of 96.62 dBA, this value exceeds the standardized Threshold Value (NAV) of 85 dBA for 8 hours of work. From the results of interviews conducted with several workers, many workers complain of hearing loss such as ringing in the ears, decreased hearing resulting in lack of concentration of the interlocutor. This study aims to analyze the effect of noise on hearing loss of PT Volex Indonesia workers. The population used in this study is all operators who work in the extruder machine area during the PVC manufacturing process. The data analysis method in this study uses quantitative methods that are processed using computer technology, namely the SPSS 21 program. The result of the regression coefficient of 19.651 means that for every noise value plus 1, hearing loss will increase by 19.651. So this regression coefficient has a significant effect so that noise affects hearing disturbance and from the results of the sig (2-tailed) correlation test 0.009 < 0.05, there is a strong correlation with the pearson correlation value of 0.771. It was concluded that there is an influence of noise on hearing loss.